Inntoning som teaterspråk: En langsiktig feedbacksløyfe-prosess med de minste - Stensen, Henriette (Peripeti, 2025)
Through practice-led research, I have developed and tested out a model for a devising process, where the intent is to develop a scenic language in cooperation with small children through a process of tuning into each other. The model’s structure is an alternation between several theatre meetings and the performer’s own devising sessions. The article introduces the term long term feedback loop to describe how a series of theatre events with the same group of children can affect the performative dynamic between audience and performers.